Bahrul Lahut Manuscripts in East Java: Study of Philology and Reconstruction of Tarekat Networks - Mashuri Mashuri (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2020)
This research discusses the Javanese text of Baḥr al-Lāhūt following a philological, epistemological, and historical approach. The aim is to study the content and history of the Baḥr al-Lāhūt and trace the Aceh–Makassar–East Java tarekat network based on the circulation of the manuscripts in East Java. The study found that the original manuscripts are in the possession of Pondok Pesantren Sumber Anyar and two other collections inSidoarjo and Pare Kediri. The textual study of the Baḥr al-Lāhūt is based on the Sumber Anyar version. Theothersurviving manuscripts are listed in the Dayah Tano Abee and the Yusuf Makassar collection. The text of the Baḥr al-Lāhūt describes the nature of God and the creation of the universe as a manifestation of Nūr Muḥammad and strongly influenced by Ibn ʿArabī’s concepts of unity of being and emanation. The distribution of the Baḥr al-Lāhūtin East Java allowed the researcher to reconstruct a network of tarekat ulama who transmitted the text through the chain of Abdurra’uf Singkili and Yusuf Makassar.